Genetic variant of MIR4300HG is associated with progression of adolescent idiopathic scoliosis in a Chinese population - Wang, Yuwen; Dai, Zhicheng; Wu, Zhichong; Feng, Zhenhua; Liu, Zhen; Sun, Xu; Xu, Leilei; Qiu, Yong; Zhu, Zezhang (Journal of orthopaedic surgery and research, 2021)
Background A recent genome-wide association study identified a susceptible locus in MIR4300HG gene that was associated with curve progression of adolescent idiopathic scoliosis (AIS) in the Japanese population. However, the association between the gene and curve progression in other populations remains unclear. Methods A cohort of 1952 AIS patients and 2495 healthy controls were included in the case-control analysis. In the case-only analysis, 747 patients were assigned to the progression group and 520 patients were assigned to the non-progression group, respectively. Rs35333564 was genotyped for all the subjects. Paraspinal muscles of 76 patients were collected for the analysis of gene expression. Chi-square test and ANOVA test were used for the intergroup comparison. Pearson correlation analysis was performed to investigate the relationship between the gene expression and curve magnitude. Results Variant rs35333564 was significantly associated with the curve severity of AIS ( p = 0.025), but not the development of AIS ( p = 0.418). Genotype GG was indicated by remarkably lower expression of MIR4300 ( p = 0.020) which was significantly correlated with curve magnitude ( p = 0.010). As a predicted target gene of MIR4300, the expression of CRTC1 was negatively correlated with MIR4300 expression ( p = 0.012, r = −0.287) and positively correlated with curve severity ( p = 0.025, r = 0.257). Conclusions The association between rs35333564 and curve progression was successfully replicated in a Chinese AIS population. CRTC1 may be the target gene of MIR4300 that plays a role in the curve progression of AIS.